Study on Brewing Quality of Naked Barley (Hodeum Vulgare L.) - Acharya, Dev Raj; Karki, Dhan Bahadur (Journal of Food Science and Technology Nepal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Proximate composition of naked barley (Hordeum Vulgare L.) and chemical characteristics of naked barley malt were analyzed. Chemical and sensorial quality of beers made from naked barley and commercial barley malts were compared. Moisture, ash, crude fat, crude protein, total carbohydrate, crude fiber and starch contents of naked barley were 8%, 1.28%, 2.82%, 11.88%, 76.03%, 1.41%, 68.53% (db) respectively. Naked barley germinated for 24 hrs had the highest amylase activity (47.13 units/100g dm). Chemical composition comparison between naked barley malt and commercial malt revealed that except percentage extract and reducing sugar other parameter viz. aroma, pH, moisture, starch, ash, specific gravity of extract, protein and amylase activity were not significantly different (p>0.05), but saccharification time, filtration rate and clarity of the extract was poor in naked barley malt compared to commercial malt. Results of chemical analysis of beers prepared from naked barley malt and commercial malt showed that pH, TSS, titrable acidity, fixed acidity, volatile acidity, esters, real extract, apparent extract, real degree of fermentation, reducing sugar, dextrin, ash and protein contents were not significantly different whereas original extract and alcohol contents were significantly higher in commercial malt beer. Sensory evaluation indicated that except mouthfeel other parameters such as appearance and clarity, color and flavor scores were higher in beer made from commercial malt than that of naked barley malt. It can be concluded that naked barley malt of satisfactory brewing quality could be prepared by following standard malting procedure adopted for barley malt. Key words: Naked barley; malt; beer; chemical characteristics; sensory quality Journal of Food Science and Technology Nepal Vol. 4, September, 2008, Page: 47-51